Unbound feet : a social history of Chinese women in San Francisco - Yung, Judy (University of California Press, 1995)
The crippling custom of footbinding is the thematic touchstone for this engrossing study of Chinese women in San Francisco. Judy Yung, a second-generation Chinese American born and raised in San Francisco, shows the stages of "unbinding" that occurred in the decades between the turn of the century and the end of the World War II, revealing that these women - rather than being passive victims of oppression - were active agents in the making of their own history
Keywords: Chinese American women -- California -- San Francisco -- History.; Women immigrants -- California -- San Francisco -- History.; San Francisco (Calif.) -- Social conditions.; Américaines d'origine chinoise -- Californie -- San Francisco -- Histoire.; Immigrantes -- Californie -- San Francisco -- Histoire.; HISTORY -- State & Local -- General.; Chinese American women; Social conditions; Women immigrants; California -- San Francisco; HISTORY / United States / State & Local / West (AK, CA, CO, HI, ID, MT, NV, UT, WY); History